A zero‐sample state evaluation model for valve‐side bushing of UHV converter transformer oriented to digital twin under attribute analysis. Issue 5 (2nd January 2023) - Li, Zheng; Liu, Kai; Lin, Mu; Xin, Dongli; Tang, Hao; Wu, Guangning
Abstract: The valve‐side bushing of the UHV converter transformer is the key equipment in the DC transmission project, and its running state directly affects the security and stability of the power system. This paper analyses the attributes of the physical entities, uses the digital twins to establish the state feature set and proposes a zero‐sample state evaluation algorithm for the valve‐side bushing. First, the geometric, materials and electrical characteristics are analyzed, and the detailed components of carrier current are obtained by empirical mode decomposition. Then, COMSOL is used to establish digital twins, verify the validity of twins with axial heat distribution of bushing, and establish a state feature set with the extreme temperature inside and outside bushing. Finally, the fuzzy clustering algorithm is used to classify the state feature set, and the similarity is used as the index to realize the zero‐sample state evaluation of the valve‐side bushing. Through the demonstration and analysis of examples, the evaluation model solves the problems of difficulty in extracting the internal features, fewer fault samples, and training difficulty, which is conducive to improving the operation and maintenance management level of power transmission equipment.